Social Microbial Transmission in a Solitary Mammal - Lauren Petrullo; Quinn Webber; Aura Raulo; Stan Boutin; Jeffrey E. Lane; Andrew G. McAdam; Ben Dantzer (Ecology Letters, 2025)
Microbial transmission is hypothesised to be a major benefit of sociality, facilitated by affiliative behaviours such as grooming and communal nesting in group‐living animals. Whether microbial transmission is also present in animals that do not form groups because territoriality limits interactions and prevents group formation remains unknown. Here, we investigate relationships among gut microbiota, population density and dynamic behavioural and spatial measures of territoriality in wild North American red squirrels ( Tamiasciurus hudsonicus ). Periods of high population density predicted population‐level gut microbial homogeneity but individual‐level diversification, alongside changes in obligately anaerobic, non‐sporulating taxa indicative of social transmission. Microbial alpha‐diversity increased with more frequent territorial intrusions, and pairs with stronger intrusion‐based social associations had more similar gut microbiota. As some of the first evidence for social microbial transmission in a solitary system, our findings suggest that fluctuations in density and territorial behaviours can homogenise and diversify host microbiomes among otherwise non‐interacting animals.